PELATIHAN PEMBUATAN DATABASE MENGGUNAKAN MICROSOFT ACCESS DI KANTOR KEPALA DESA PALUH SIBAJI KECAMATAN PANTAI LABU - Panjaitan, Melda; Hutagalung, Siti Nurhabibah (Jurnal Masyarakat Indonesia (Jumas), 2025)
There needs to be data stored on an access, where the data can be accessed and grouped according to its use. In the database application at the office of the Head of Paluh Sibaji Village, Pantai Labu District, a mindset is formed to form independence, creativity in designing a database system that can be applied in daily life, especially in the world of work. There is a need for assistance and motivation in opening up insights to study and pursue the field of databases, where the evaluation benchmarks of community service activities can make the design of attendance databases, storage of goods to sales